Recursive Health Care Structures and Choice in the Manner of Our Dying: An Auto-Ethnographic Account. (March 2016) - Wackers, Ger
Science has shaped our understanding of the diseases we are diagnosed with. Medical treatment has transformed their natural courses. The law has married medical knowledge and experience to the legal competence of physicians to make ultimate decisions for the patient at the end of life. When it is our time to die, we will confront a pre-structured health care landscape affording some courses of action while limiting others. In this article, I provide an auto-ethnographic account of the dying of one woman, my wife, diagnosed with ovarian cancer. It speaks of our meeting with oncology, her refusal of aggressive treatment, and the palliative care allies we found for her way of dying. It also speaks of the opportunities for choice in dying that emerge when participants in the care collective accept that one of them must die while the others live on.